2018
DOI: 10.1002/pds.4448
|View full text |Cite
|
Sign up to set email alerts
|

GOLD assessment of COPD severity in the Clinical Practice Research Datalink (CPRD)

Abstract: Using our adaptation of the GOLD 2016 COPD severity classification, the information in the Clinical Practice Research Datalink allowed us to ascertain COPD severity in approximately 75% of patients with COPD. Algorithms that include medication use tend to misclassify patients with the extreme COPD severity categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…2 As the pathophysiology of irreversible disease 3 causes airway limitation that develops into fibrosis, enlarged alveolar affecting gas exchange and diffusion 4 can be identified with a clinical pulmonary function test. 5 Strong evidence reported that chronic inflammation and recurrent infection are related to higher oxidants in COPD patients, 6 which is consistent with a previous study on the levels of nitric oxide and lipid peroxide in such patients when compared to healthy people, 7 as well as another report on the high level of malondialdehyde (MDA) from lipid peroxidation and low level of glutathione (GSH) or total antioxidant capacity (TAC). 8 Although there is less evidence to confirm the relationship between high oxidative stress and low physical function, dominant skeletal dysfunction, muscle atrophy and sarcopenia have been reported, 9 but unfavorable function and low physical activity were presented in most COPD patients.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…2 As the pathophysiology of irreversible disease 3 causes airway limitation that develops into fibrosis, enlarged alveolar affecting gas exchange and diffusion 4 can be identified with a clinical pulmonary function test. 5 Strong evidence reported that chronic inflammation and recurrent infection are related to higher oxidants in COPD patients, 6 which is consistent with a previous study on the levels of nitric oxide and lipid peroxide in such patients when compared to healthy people, 7 as well as another report on the high level of malondialdehyde (MDA) from lipid peroxidation and low level of glutathione (GSH) or total antioxidant capacity (TAC). 8 Although there is less evidence to confirm the relationship between high oxidative stress and low physical function, dominant skeletal dysfunction, muscle atrophy and sarcopenia have been reported, 9 but unfavorable function and low physical activity were presented in most COPD patients.…”
Section: Introductionsupporting
confidence: 85%
“…8 Although there is less evidence to confirm the relationship between high oxidative stress and low physical function, dominant skeletal dysfunction, muscle atrophy and sarcopenia have been reported, 9 but unfavorable function and low physical activity were presented in most COPD patients. 5 Moreover, high oxidative stress reportedly related to high inflammation status in COPD patients. 10 For instance, previous reports proved that overexpression of tumor necrotic factor-alpha (TNF-∝) in the lung induced the release of superoxide radicals from the macrophage or neutrophils, 11 and a dominantly high level was found in the blood of COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…COPD-specific measures were: COPD Assessment Test (CAT) scale, modified Medical Research Council (mMRC) dyspnea scale, lung function (forced expiratory volume in the first second [FEV1] % predicted), and number of previous COPD exacerbations during the 18-month baseline period (moderate or severe, as defined by Punekar et al [28]). These were combined as shown in Supplementary Figure S1 to define COPD severity as significant or non-significant [29,30].…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…In prevalence research, the lack of symptoms criteria is challenging. In fact, in the ABCD classification of COPD, MRC > 2 is required to be classified as B or D . Therefore, people with COPD classified as A or B, by definition, have an MRC score of 1–2 and therefore the symptom threshold of MRC score > 2 used in the study may be too high.…”
Section: Discussionmentioning
confidence: 99%